Pengembangan Video Pembelajaran pada Materi Tata Surya untuk Meningkatkan Motivasi Belajar Siswa - Nurhatmi, Jules; Sepriyadi, Toni; Murtini, Murtini (Jurnal Gentala Pendidikan Dasar, 2025)
This research aims to produce learning video media on solar system material, which was tested for media feasibility validity, usefulness, and the improvement of student learning motivation as an implication of using the learning media. The research method used was Research and Development (R&D) employing the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). This study was conducted at MI Nahdlathut-Thullab in Jambi City, involving 35 sixth-grade students and the class teacher. The feasibility percentage from media experts was initially 87% and increased to 95% after revisions. The feasibility percentage from material experts was 95% and reached 100% after revisions. The teacher response percentage obtained was 100%. The results of individual trials showed 87% for both motivation and media aspects. Small group trials yielded 94.6% for the motivation aspect and 100% for the media aspect. Large group student trials obtained 93% for the motivation aspect and 91% for the media aspect. Based on these percentages, it is concluded that the solar system learning video met very feasible criteria for use and positively influenced the increase in student learning motivation.